The Role of Teachers In Improving The Learning Motivation of Class 1 KMI In Tafsir Subject at Darussalam Gontor Islamic Boarding School, Ponorogo, Indonesia. - Moh Mukhlas; Zuhrufan Failasufa (Educan : Jurnal Pendidikan Islam, 2019)
Darussalam Gontor Modern Islamic Boarding School is one of the educational institutions with the largest Islamic boarding school base in Indonesia. Educational institutions that use the Mu'allimin Al-Islamiyyah Kulliyyatul system provide an important role for teachers to educate their students in the classroom. Class 1 is the initial level of the students in studying at this institution. The subject taught at this level becomes the basis or principle for learning subject at the next level. So it has been ascertained that the efforts and role of the teacher are very dominant to support success and to increase the motivation of the student at this level. Especially in Tafsir subject. Because in the learning, this subject has a little difference with the Tafsir subject at the next level and requires the effort and role of the teacher in the success of learning the subject. The purpose of this study is to find out : 1) the role of the teacher in increasing students' motivation in class 1 KMI in Tafsir subject, 2) Teaching methods used by teachers in learning Tafsir subject for class 1 of KMI Darussalam Gontor Modern Islamic Institution